Erythroderma Suspected Caused by Sambiloto (Andrographis paniculata): A Case Report - Revinanda Venincia Pangaribuan; Dina Arwina Dalimunthe; Ade Arhamni (Indonesian Journal of Global Health Research, 2025)
Erythroderma, or Exfoliative Dermatitis (ED), is a serious dermatological emergency marked by erythema and scaling over more than 90% of the body surface area. Although etiologies are diverse, drug reactions remain a major cause. Beyond conventional pharmaceuticals such as antibiotics, antivirals, anti-inflammatory agents, cardiac drugs, and chemotherapeutics, herbal remedies have also been linked to hypersensitivity reactions. Sambiloto (Andrographis paniculata), a traditional antidiabetic widely used in Southeast Asia, has been reported to trigger severe cutaneous adverse reactions, including erythroderma. We present the case of a 53-year-old woman with diabetes mellitus who developed generalized erythematous macules, scaling, severe pruritus, fever, chills, and fatigue four days after consuming a Sambiloto decoction. She denied the use of other medications. Clinical findings supported by histopathological analysis confirmed erythroderma. Management involved discontinuation of the suspected herbal, systemic corticosteroids, antihistamines, moisturizers, antibiotics, and glucose control, leading to marked improvement within eight days. This case highlights that drug-induced erythroderma often has an acute onset and rapid course. Despite their reputation for safety, herbal medicines may provoke severe hypersensitivity reactions with potentially life-threatening outcomes. Comprehensive drug history-taking, including traditional remedies, is therefore essential in evaluating patients with exfoliative dermatitis. The objective of this report and journal is to raise awareness of herbal-induced erythroderma and to contribute to the growing body of evidence regarding the risks of traditional therapies. Early recognition and prompt withdrawal of the causative agent remain critical for preventing recurrence and improving patient outcomes.